Android Based Mind Mapping Learning Media to Improve Students' Understanding of National Income - Harahap, Syaiful Bagus Rahmadi; Ghofur, Muhammad Abdul (Universitas Veteran Bangun Nusantara, 2020)
The purpose of this study was to develop an Android-based mind mapping learning media for national income material to improve students' understanding of IPS Class XI specialization. This Development Research uses Analysis, Design, Development, Implementation, and Evaluation. Based on the results of trials that can be obtained that understood by students increases. The pre-test and post-test results increased by 30.6%, and the test results prove a statistically significant difference. The implications of this study confirm the application of the concept of mind mapping in interactive learning media that helps improve student learning outcomes, especially in material with complex concept construction.